The effect of a hand hygiene intervention on the behaviour, practices and health of parents of preschool children in South Africa. (November 2022) - Lange, Samantha; Barnard, Tobias George; Naicker, Nisha
Introduction: Diarrhoea and upper respiratory diseases are a leading cause of child mortality in children under 5 years of age both in South Africa and worldwide. Hand hygiene (HH) interventions play a critical role in reducing HH-related diseases, and the inclusion of all stakeholders in such interventions has improved the success of such interventions. The purpose of this study is to determine the effect of an HH intervention on the behaviour, practices, and health of parents of preschool children. Methodology: Seventeen preschools were randomly selected and placed into intervention (IG = 8) and control groups (CG = 9). Parents ( N = 191) were requested to complete questionnaires both pre- and postintervention. An intervention was applied to IG preschool respondents. The data were analysed and compared pre- and postintervention between IG and CG. Results: Parents of IG showed a significant difference pre- and postintervention in HH practices such as washing hands after coughing and sneezing, and after using the toilet while parents in CG also indicated significant differences in HH practices of washing hands after coughing and sneezing, and after wiping children's noses. Postintervention, IG families reporting runny tummies were significantly less than pre-intervention and a decrease in doctor's visits. There was a 5% improvement of all HH practices in both IG and CG. Conclusion: Over 90% of parents in both groups washed hands after using the toilet, both pre- and postintervention. All HH practices for both groups showed increases both pre- and postintervention. By making use of available resources and regular communication with parents of preschoolers they are able to make the small changes necessary to improve their HH and that of their families.